Cluster analysis based on biochemical constituents in paprika like chillies (Capsicum annuum L.) - N K Leela, K Jayarajan, Kiptoo Geoffry, P Gobinath, T J Zachariah, K N Shiva, (Journal of Spices and Aromatic Crops, 2014)
Chillies and paprika like chillies (Capsicum annuum L.) belonging to Solanaceae, is a source of natural colour, widely used in the food industry and is in great demand in the international market. Twenty-four accessions belonging to Indigenous Collections of Byadagi Dabbi (ICBD) and others were analyzed for biochemical constituents from leaf. Biochemical constituents studied were total carbohydrate, starch, reducing sugars, total free amino acids, phenol and protein. The accessions were compared for the isozymes viz., peroxidase, super oxide dismutase and poly phenol oxidase in the leaf, besides, leaf protein using SDS-PAGE. The dendrogram showing the relationship among the accessions for leaf biochemical constituents and colour value of fruits formed six clusters. Colour value ranged from 109 to 353 ASTA units. The accessions ICBD-11 and ICBD-19 possessed highest colour value. Accession ICBD-24 was distinctly different from others. Accessions in each cluster had almost uniform colour value and uniform isozyme profile. The accession ICBD-24 was a Coorg collection and ICBD-11 and ICBD-19 were from Dharwad district of Karnataka. Significant positive correlation was observed between colour value and total free amino acids, total protein, total phenol and polyphenol oxidase in paprika like chillies.